1998
DOI: 10.1530/jrf.0.1140025
|View full text |Cite
|
Sign up to set email alerts
|

Spermadhesins of the AQN and AWN families, DQH sperm surface protein and HNK protein in the heparin-binding fraction of boar seminal plasma

Abstract: Heparin-binding proteins (designated BHB-2-BHB-9) were isolated from boar seminal plasma by affinity chromatography on heparin immobilized on polyacrylamide gel, followed by reverse phase HPLC. According to their N-terminal amino acid sequences, BHB-3-BHB-5 belong to the AQN family of spermadhesins and BHB-7-BHB-9 to the AWN family. BHB-6 is composed of two different proteins. The dominant protein (14 kDa) has the N-terminal amino acid sequence HNKQEGRDHD that is identical to the sequence of human semenogelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 22 publications
(34 reference statements)
4
54
0
Order By: Relevance
“…N-terminal sequence of DQH protein matches exactly the determined N-terminal sequence~32 amino acid residues! of pAIF-1~Hadjisavas et al, 1994;Jonáková et al, 1998!. On the other hand, it is obvious that the DQH protein described here and the pB1 protein described previously belong to the same family of seminal plasma proteins as bovine BSP A1, BSP A3 Seidah et al, 1987!, andstallion HSP-1~Calvete et al, 1995!. These proteins are all members of the large family of cell and matrix adhesion proteins, which includes seminal plasma proteins, colagenases, fibronectins, blood coagulation factors, and large cell surface receptors such as the macrophage mannose receptor, and the cation independent mannose-6-phosphate receptors~Hadjisa-vas et al, 1994!. Unlike in seminal plasma proteins, where the tandemly arranged fibronectin type II repeats encompass most of the protein sequence, in the other proteins of this family, this repeat represents only a small portion of the entire protein sequence.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…N-terminal sequence of DQH protein matches exactly the determined N-terminal sequence~32 amino acid residues! of pAIF-1~Hadjisavas et al, 1994;Jonáková et al, 1998!. On the other hand, it is obvious that the DQH protein described here and the pB1 protein described previously belong to the same family of seminal plasma proteins as bovine BSP A1, BSP A3 Seidah et al, 1987!, andstallion HSP-1~Calvete et al, 1995!. These proteins are all members of the large family of cell and matrix adhesion proteins, which includes seminal plasma proteins, colagenases, fibronectins, blood coagulation factors, and large cell surface receptors such as the macrophage mannose receptor, and the cation independent mannose-6-phosphate receptors~Hadjisa-vas et al, 1994!. Unlike in seminal plasma proteins, where the tandemly arranged fibronectin type II repeats encompass most of the protein sequence, in the other proteins of this family, this repeat represents only a small portion of the entire protein sequence.…”
mentioning
confidence: 61%
“…It has been shown that boar seminal plasma contains proteins that are not members of AQN and AWN families~Fernlund et al, 1994;Hadjisavas et al, 1994;Jonáková et al, 1998!. One of them, the phosphorylcholine-binding protein pB1, has been recently characterized~Calvete et al, 1997!.…”
mentioning
confidence: 99%
“…Mannose-binding sites and AQN-1 molecules (Jonakova et al, 1998) are localized over the acosomal region of the sperm. GNA-binding proteins of the oviductal membrane bind to the same region of the sperm surface when tested by fluorescence microscopy after treatment of a sperm suspension with the biotinylated protein fraction (Fig.…”
Section: Candidate Molecules Involved In Sperm-oviduct Interactionsmentioning
confidence: 99%
“…These fractions were subjected to CE. Individual protein components of these fractions were obtained using RP-HPLC separation as described previously [14]. These individual proteins were used as standards for CE.…”
Section: Samplesmentioning
confidence: 99%
“…Among the ligands used, immobilized heparin is often applied to separate H+ and heparin-nonbinding fraction of seminal plasma (H -) proteins [7,13,14]. Affinity techniques not only are useful for the protein isolation but also represent a valuable and essential tool for the study and analysis of binding properties of protein components that participate in the fertilization process.…”
Section: Introductionmentioning
confidence: 99%